Analisis Keamanan DHCP Menggunakan RADIUS Accounting - Elisa Stefano Franli Purun; Dian Widiyanto Chandra (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Every computer needs and must have an IP Address to connect with other computer network users, the IP Address will be automatically distributed to network users using the Router as a DHCP Server. In addition to DHCP, the Router has a DHCP Accounting service that can improve network security with AAA and RADIUS Server features that can be implemented with Freeradius. DHCP Accounting has accounting capabilities for secure START and STOP message transmission, but the flash memory capacity on the C2691 router is around 32 MB, making the DHCP Accounting service not run optimally if it has many users. Using MySQL as a database can be a solution to this problem. When using the DHCP Accounting feature, data from DHCP Accounting will be sent and centralized on Freeradius. Accounting data centralized on Freeradius will be stored using a MySQL database so that the available storage space will be much larger and can accommodate more data from DHCP Accounting, as well as monitoring the network so as to improve network security for users.